2019
DOI: 10.1039/c9ra08231j
|View full text |Cite
|
Sign up to set email alerts
|

Alchemilla vulgaris agg. (Lady's mantle) from central Balkan: antioxidant, anticancer and enzyme inhibition properties

Abstract: The current study was designed to evaluate the phytochemical profile and biological properties of extracts of Alchemilla vulgaris from Southeast Serbia which was traditionally used to alleviate and treat many diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 55 publications
3
31
0
4
Order By: Relevance
“…A number of food and medicinal plants have been processed for primary-and secondary-metabolite determination [22] to establish a possible link between their phytocomponents and beneficial bioactivities. It is well known that the polyphenolics and flavonoids, as well as their glycosides, are responsible for antioxidant, anticancer, and cardioprotective activity [23]. The HPLC-PDA analysis results showed that the leaf and stem extracts contained diverse phenolic compounds, with epicatechin, rutin, and catechin as the most abundant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of food and medicinal plants have been processed for primary-and secondary-metabolite determination [22] to establish a possible link between their phytocomponents and beneficial bioactivities. It is well known that the polyphenolics and flavonoids, as well as their glycosides, are responsible for antioxidant, anticancer, and cardioprotective activity [23]. The HPLC-PDA analysis results showed that the leaf and stem extracts contained diverse phenolic compounds, with epicatechin, rutin, and catechin as the most abundant.…”
Section: Discussionmentioning
confidence: 99%
“…The HPLC-PDA analysis results showed that the leaf and stem extracts contained diverse phenolic compounds, with epicatechin, rutin, and catechin as the most abundant. Plants contain different classes of phenols, including polyphenols, flavonoids, phenolic acids, stilbenes, and lignins, which are involved in the protection against and cure of diseases such as cancers, cardiovascular diseases, diabetes, and others [23,24]. Flavonoids are the most abundant polyphenol in human diets.…”
Section: Discussionmentioning
confidence: 99%
“…It might be added that aside from wound or burn healing, collagenase inhibitors might be useful in the treatment of other skin-related diseases, such as dermatitis, acne, urticarial, or photoaging (Mandrone et al, 2018). Also, Vlaisavljević et al (2019) revealed amylase and tyrosinase inhibitory effects of A. vulgaris, which might be related to antidiabetic and skin-related diseases (Vlaisavljević et al, 2019). Improvement of wound healing of lady's mantle was also connected to its anti-inflammatory effects (Ghedira et al, 2012), which were recently confirmed in the study of Boroja et al (2018) where a methanolic extract of aerial part of this plant (in the concentration of 50 µg/mL) was shown to inhibit the activity of COX-1 enzyme by 44.4 %, whereas the inhibition of COX-2 was higher (63.6 %) (Boroja et al, 2018).…”
Section: Wound Healingmentioning
confidence: 99%
“…Such results were ascribed to the high amount of polyphenols in the tested extract, where in the one obtained from Alchemillae herba the major identified compound was ellagic acid (Boroja et al, 2018). Similarly, Vlaisavljević et al (2019) used several antioxidant assays (DPPH, ABTS, CUPRAC, phosphomolybdenum, metal chelating, FRAP) to compare the antioxidant potential of methanolic, ethanolic, ethyl-acetate, and water extracts of lady's mantle. The authors found a strong correlation between total phenolic content and antioxidant activity, with ethyl-acetate extract having the highest content of total phenol compounds (9.65 mg GAE/g) and therefore the highest antioxidant activity.…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation